Coefficient Inequality for Certain New Subclasses of Sakaguchi Type Function Related to Sigmoid Functions - Srutha Keerthi, B.; Raja, Bhuvaneswari (International Journal of Engineering and Technology, 2018)
The question of the present paper is to get starting coefficients| | |,| |,| |, upper limits of | and second Hankel determinant related with a class of systematic univalent capacity of sakaguchi compose work identified with sigmoid capacity in the open unit plate âˆ†. Different creators as Abiodum, Tinuoye Oladipo, Murugu sundaramoorthy et. al., and Olatunji have contemplated sigmoid capacity for various classes of systematic and univalent capacities. Our outcomes fills in as a speculation toward this path and it conceives an offspring some current subclasses of capacities.Â Â